Acute Myeloid Leukaemia Unmasked by Paraplegia: A Case Report - Krupa Bhanushali; Revat Meshram; Amar Taksande; Aditya Jain (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Acute Myeloid Leukaemia (AML) is a rapidly progressive myeloid neoplasm that is characterised by clonal expansion of immature myeloid lineage cells, known as blasts in the bone marrow and peripheral blood. It is known to present with pallor, bleeding tendencies and infections. However, Extra Medullary (EM) presentations involving the central nervous system are rare and can delay clinical diagnosis. Hereby, the authors report a case of 14-year-old male child who had a unique presentation of acute myeloid leukaemia. His initial symptoms were indicative of a central nervous system disease, and later the child was diagnosed to have acute myeloid leukaemia with spinal metastasis. A case of AML which does not routinely present with lower limb weakness and bowel or bladder dysfunction can be isolated with this case report and a crucial diagnosis can be caught early on. The present case underscores the critical need for maintaining high suspicion for haematological malignancies in children presenting with neurological deficits. It also highlights the different dimensions of the disease pathology and the disease’s rapid progression to metastasis. The key role of diagnostic imaging to isolate metastasis has also been focused on.